PENERAPAN LITERASI MEDIA DALAM KETERAMPILAN PEMANFAATAN MEDIA PADA ERA TEKNOLOGI INFORMASI DI PERPUSTAKAAN POLITEKNIK NEGERI SRIWIJAYA PALEMBANG - Sulistya, Ika; Wahidi, Ahmad (DE FACTO : Journal Of International Multidisciplinary Science, 2024)
In terms of finding information needs in the library, users try to see the information search strategy used to meet their needs. In determining diverse information needs in this era of information technology, people or users are asked to be more careful, responsive, and critical of randomly scattered information. It is important to apply media literacy in order to recognize, examine, and assess information from the media in order to find the right, accurate, reliable and up-to-date information. The research method used is descriptive qualitative. The results of the research in this scientific article are that the library users search for information in the library by applying literacy in media utilization skills in this era of information technology. Then the selection of data to be used by distinguishing and assessing media capacity responsively so that people can use the media according to their needs. Furthermore, the usefulness of this research is as a scientific guideline related to the implementation of media literacy in media utilization skills in the era of information technology and the information search process in finding user information needs.